Superhydrophobic electrosprayed PTFE - Burkarter, E. (2007)
This paper shows the deposition of superhydrophobic PTFE (polytetrafluoroethylene) films on FTO (fluorine doped tin oxide) coated glass slides, employing the electrospray technique, using a commercial PTFE particle suspension in water. Water contact angles as high as 167° were measured on the PTFE surface. Water drop sliding angles at 2° show a very low contact angle hysteresis. Scanning electron and atomic force microscopy images show the typical rough micro/nanostructure required for superhydrophobicity. © 2007 Elsevier B.V. All rights reserved.